Histomorphologisch definierte Nierenzellkarzinome 2025: Aktuelle WHO-Klassifikation und sich abzeichnende zukünftige Subtypen - Stöhr, Christine; Fiegl, August; Bercebal, C.; Agaimy, Abbas; Hartmann, Arndt (Die Pathologie, 2025)
BACKGROUND: The latest edition of the WHO classification of urinary and male genital tumours was published in 2022. The revision was based on the newest scientific literature. This article summarizes the updated recommendations regarding the classification of histomorphologically defined tumours. RESULTS AND CONCLUSIONS: The current edition of the WHO classification made some adjustments on the classification of histomorphologically defined tumour types. Papillary renal cell carcinoma is no longer categorized into two subtypes. Also, the new classification recognized the benign nature of clear cell papillary tumours, which are no longer regarded as carcinomas. Finally, several emerging renal tumours were introduced.
EVALuna2:585361

Molekular definierte Nierenzellkarzinome 2025 - Stöhr, Christine; Fiegl, August; Bercebal, C.; Agaimy, Abbas; Hartmann, Arndt (Die Pathologie, 2025)
BACKGROUND: The latest edition of the WHO classification of urinary and male genital tumours was published in 2022. The revision was based on the newest scientific literature. This article summarizes the updated recommendations regarding the classification of molecularly defined tumours. RESULTS AND CONCLUSIONS: The current edition of the WHO classification of tumours introduced the new category of molecularly defined tumours. This category includes TFE3-rearranged RCC, TFEB-altered RCC, ELOC-mutated RCC, FH-deficient RCC, SDH-deficient RCC, ALK-rearranged RCC and SMARCB1-deficient RCC. The change reflects the importance of the respective alterations with regard to tumour biology and future treatment options. Simultaneously, the diagnosis of these tumours, which sometimes can show equivocal morphologies, is facilitated.
EVALuna2:585356